1998
DOI: 10.7748/ns.12.43.49.s55
|View full text |Cite
|
Sign up to set email alerts
|

Numeracy skills for intravenous calculations

Abstract: Aims and intended learning outcomes: This article covers the numeracy skills required in the administration of intravenous (IV) therapy in the acute setting. It begins by considering everyday practice with straightforward prescriptions and progresses to more complex calculations. The article also encourages the practitioner to consider other related features of IV therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…During the last years of the pharmacy Program, numeracy calculations performed by students are applicable to day-to-day life rather than the basic calculations used for dose measurements (14). In contrast to our observations, previous studies have reported that first-year midwifery and nursing students had relatively lower mathematical ability (45)(46)(47) which hints toward the fact that students entering midwifery and nursing courses lack basic numeracy skills and concepts which…”
Section: Discussioncontrasting
confidence: 99%
“…During the last years of the pharmacy Program, numeracy calculations performed by students are applicable to day-to-day life rather than the basic calculations used for dose measurements (14). In contrast to our observations, previous studies have reported that first-year midwifery and nursing students had relatively lower mathematical ability (45)(46)(47) which hints toward the fact that students entering midwifery and nursing courses lack basic numeracy skills and concepts which…”
Section: Discussioncontrasting
confidence: 99%
“…In the IV therapy methodology, the symbol Gtt represents the drop per minute (min), and the drop factor is defined as the drop per mL. Therefore, the flow rate (cc/hr) can be calculated as three times the Gtt (drop/min) if the drop factor (drop/mL) is 20 [31], [32]. In this study, we prefer the duration of one rotation to be less than 2.0 s to ensure that the flow rate can be selected within 0-90 cc/hr, as expressed by Eq.…”
Section: Optimization Of the Dropping Countmentioning
confidence: 99%